Mengembangkan Kerjasama Tim dalam Pengelolaan Pendidikan Islam di Era Digital - Aris, Maifalinda; Jamilus, Jamilus (Indo-MathEdu Intellectuals Journal, 2024)
Teamwork in the management of Islamic education in the digital era is the focus in this research. This study aims to analyze effective methods and strategies in developing teamwork in Islamic educational institutions. A qualitative approach was used by conducting in-depth interviews and observations of Islamic education management teams in several institutions. Data analysis is carried out in depth using qualitative data analysis consisting of data reduction, data presentation, and conclusion drawing. The results showed that cooperation skills training, multidisciplinary team building, use of collaborative platforms, community engagement, and regular evaluations were key factors in improving teamwork. These findings make an important contribution to practical understanding in the management of Islamic education in the digital age, as well as provide practical recommendations for educational institutions to improve teamwork and quality of education.